Going beyond LTM in the MTL: a synthesis of neuropsychological and neuroimaging findings on the role of the medial temporal lobe in memory and perception. - Graham, K; Barense, MD; Lee, A (2010)
Studies in rats and non-human primates suggest that medial temporal lobe (MTL) structures play a role in perceptual processing, with the hippocampus necessary for spatial discrimination, and the perirhinal cortex for object discrimination. Until recently, there was little convergent evidence for analogous functional specialisation in humans, or for a role of the MTL in processes beyond long-term memory. A recent series of novel human neuropsychological studies, however, in which paradigms from the animal literature were adapted and extended, have revealed findings remarkably similar to those seen in rats and monkeys. These experiments have demonstrated differential effects of distinct stimulus categories on performance in tasks for which there was no explicit requirement to remember information across trials. There is also accruing complementary evidence from functional neuroimaging that MTL structures show differential patterns of activation for scenes and objects, even on simple visual discrimination tasks. This article reviews some of these key studies and discusses the implications of these new findings for existing accounts of memory. A non-modular view of memory is proposed in which memory and perception depend upon the same anatomically distributed representations (emergent memory account). The limitations and criticisms of this theory are discussed and a number of outstanding questions proposed, including key predictions that can be tested by future studies.